2015
DOI: 10.3346/jkms.2015.30.5.552
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Partially Alleviates the Bite Force Reduction in a Mouse Model of Temporomandibular Joint Pain

Abstract: Temporomandibular joint (TMJ) disorder is clinically important because of its prevalence, chronicity, and therapy-refractoriness of the pain. In this study, we investigated the effect of infliximab in a mouse model of TMJ pain using a specially-engineered transducer for evaluating the changes in bite force (BF). The mice were randomly divided into three groups (7 mice per group): the control group, the complete Freund's adjuvant (CFA) group, and the infliximab group. BF was measured at day 0 (baseline BF). Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…TMDs are also associated with mastication-related pain. 13,14 When TMDs occur due to tissue injury in the relevant structures, mastication becomes painful, leading to decreased bite forces and the eventual reduction in food intake. 9,34,35 It has been suggested that the measurement of bite force may represent a more clinically relevant feature of TMDs than the assessment of orofacial mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TMDs are also associated with mastication-related pain. 13,14 When TMDs occur due to tissue injury in the relevant structures, mastication becomes painful, leading to decreased bite forces and the eventual reduction in food intake. 9,34,35 It has been suggested that the measurement of bite force may represent a more clinically relevant feature of TMDs than the assessment of orofacial mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…9,34,35 It has been suggested that the measurement of bite force may represent a more clinically relevant feature of TMDs than the assessment of orofacial mechanical allodynia. 13,14 Recently, several innovative methods were developed to directly test bite force. 13,14,36 Dolan et al 37 used a dolognawmeter to quantify the gnawing functions of three mouse models of orofacial pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infliximab is a chimeric immunoglobulin‐G1 monoclonal antibody that targets TNF‐α, most commonly used in immunosuppressive treatments and reportedly contributes to inflammation symptoms . Therefore, the objective of this study was to evaluate the role of TNF‐α in orofacial discomfort in an occlusal dental interference model in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it should be noted that despite the high "incidence" (78.3%) of mini-implant penetration in the infrazygomatic crest, there was an overall success rate (96.7%) higher than in previous studies with miniimplants installed in different sites. 5 Jia et al 1 well known that clinical success depends on initial mechanical stability and proper loading. 6 It was highlighted that no patient complained of clinical symptoms; there was no detected mobility, and all patients had stable anchoring performance until the end.…”
mentioning
confidence: 99%